Il ruolo della SPECT in associazione a iofupane nella diagnosi della Malattia di Parkinson: i risultati di un’esperienza - Antonini, Angelo; Colombo, Giorgio L. (Farmeconomia. Health economics and therapeutic pathways, 2002)
According to the latest data, in Italy 200.000 patients are affected by the Parkinson’s Disease, and the trend is bound to go up. Generally the diagnosis, crucial in this pathology, is based on the clinic observation. But the absence of typical signs or symptoms increases the possibility of diagnostic mistakes. Ioflupane (DATSCAN ®) is a new diagnostic agent indicated for detecting loss of functional dopaminergic neuron terminals in the striatum of patients with clinically uncertain Parkinsonian Syndromes. The use of Ioflupane (DATSCAN ®) in association with the single-photon emission computed tomography (SPECT) allows to improve the diagnosis. Applying systematically this diagnostic model could cause a significant reduction in hospedalization cost, with less trouble for patients and a better quality of life. Aim of this study is to show the clinical and economic consequences of the use of Ioflupane (DATSCAN â) in association with SPECT as a new standard for the diagnosis of Parkinson’s Disease, considering the perspective of the National Heath System (NHS) and a single hospital structure.